CORRUPTION INSTITUTION GOVERNANCE: IMPLEMENTATION OF ACCOUNTABILITY PRINCIPLES IN CORRECTIONAL INSTITUTION MANAGEMENT - Vita Nurul Fathya (Polteknik Ilmu Pemasyarakatan, 2018)
Correctional institution as a government agencyis obliged to account for any decisions and measures it takes. Therefore, the management of correctional institutions should be conducted by accountable persons so thatthe duties and functions can be implemented effectively. This article refers to some views on how to implement the principle of accountability in managing correctional institutionas input for application in Indonesia. Topic of discussion covers aspects of prison management, the importance of prison accountability, accountability proses, the characteristics of accountable prison manager, how to encourage accountability, and the challenges in prison accountability.